Nitric Oxide-Mediated Induction of Dispersal in Pseudomonas aeruginosa Biofilms Is Inhibited by Flavohemoglobin Production and Is Enhanced by Imidazole - Zhu, Xinyi (2018)
The biological signal molecule nitric oxide (NO) was found to induce biofilm dispersal across a range of bacterial species, which led to its consideration for therapeutic strategies to treat biofilms and biofilm-related infections. However, biofilms are often not completely dispersed after exposure to NO. To better understand this phenomenon, we investigated the response of Pseudomonas aeruginosa biofilm cells to successive NO treatments. When biofilms were first pretreated with a low, noneffective dose of NO, a second dose of the signal molecule at a concentration usually capable of inducing dispersal did not have any effect. Amperometric analysis revealed that pretreated P. aeruginosa cells had enhanced NO-scavenging activity, and this effect was associated with the production of the flavohemoglobin Fhp. Further, quantitative real-time reverse transcription-PCR (qRT-PCR) analysis showed that fhp expression increased by over 100-fold in NO-pretreated biofilms compared to untreated biofilms. Biofilms of mutant strains harboring mutations in fhp or fhpR, encoding a NO-responsive regulator of fhp, were not affected in their dispersal response after the initial pretreatment with NO. Overall, these results suggest that FhpR can sense NO to trigger production of the flavohemoglobin Fhp and inhibit subsequent dispersal responses to NO. Finally, the addition of imidazole, which can inhibit the NO dioxygenase activity of flavohemoglobin, attenuated the prevention of dispersal after NO pretreatment and improved the dispersal response in older, starved biofilms. This study clarifies the underlying mechanisms of impaired dispersal induced by repeated NO treatments and offers a new perspective for improving the use of NO in biofilm control strategies.